Languages alive essays dedicated to Jürgen Dassow on the Occasion of His 65th Birthday - Kutrib, Martin; Truthe, Bianca (Lecture Notes in Computer Science,, 2012)
This festschrift volume, published in honor of Jürgen Dassow on the occasion of his 65th birthday, contains 19 contributions by leading researchers, colleagues, and friends. Covering topics on picture languages, cooperating distributed systems of automata, quantum automata, grammar systems, online computation, word equations, biologically motivated formal systems, controlled derivations, descriptional complexity, as well as 'classical' topics of automata and language theory, the articles presented span the range of the scientific work of Jürgen Dassow.